Application of Robotics Technology in Clinical Practice in India - Karandikar, Pratibha M.; Tayade, Motilal C. (Asian Journal of Medical Sciences, 2013)
Background: The field of mechanical engineering in association with electronics and computer science concerned with developing robotic devices that can move and react to sensory input. However the implementations and application of robotics in clinical practice was really a question? We planned to study the assessment of awareness, will and work level of medical robotics from medical professionals in clinical practice in India. Study Design: We used self prepared model questioner containing information related to applications, awareness, will etc. of medical professionals for application of medical robotics in clinical practice. The questioner was approved by IJBAMR Forum, Pune, India. The data was collected during June 2012 to January 2013. Such 220 questionnaires were filled and analyzed. Observations and Results: Only 1.36 % professionals observed with professional training. It was also observed that, only 54.54% professionals were known about current aspects about robotics application & knowledge regarding training centers. Conclusion: It is promising fact found in study that 88.63% professionals were very excited and willful for the application of robotics in their practice in future. From our study, it is concluded that there is noted a huge lake of awareness regarding application of medical robotics technology in Indian medical professionals. DOI: http://dx.doi.org/10.3126/ajms.v5i1.7991 Asian Journal of Medical Science Vol.5(1) 2014 pp.29-33